AIDSVAX protein boost improves breadth and magnitude of vaccine-induced HIV-1 envelope-specific responses after a 7-year rest period. Issue 33 (30th July 2021) - Huang, Yunda; Seaton, Kelly E.; Casapia, Martin; Polakowski, Laura; De Rosa, Stephen C.; Cohen, Kristen; Yu, Chenchen; Elizaga, Marnie; Paez, Carmen; Miner, Maurine D.; Kelley, Colleen F.; Maenza, Janine; et al.
Abstract: Background: Eliciting durable humoral immunity with sufficient breadth and magnitude is important for HIV-1 vaccine design. The HVTN 114 vaccine trial evaluated different boost regimens administered after a 7-year rest period in participants previously enrolled in HVTN 205, who received either three MVA/HIV62B (MMM) or two DNA and two MVA/HIV62B (DDMM) injections; both vaccines expressed multiple HIV-1 antigens in non-infectious virus-like-particles. The primary objective of HVTN 114 was to assess the impact of a heterologous gp120 protein AIDSVAX B/E boost on the magnitude, breadth and durability of vaccine-induced immune responses. Methods: We enrolled 27 participants from HVTN 205 into five groups. Eight participants who previously received MMM were randomized and boosted with either MVA/HIV62B alone (T1; n = 4) or MVA/HIV62B and AIDSVAX B/E (T2; n = 4). Nineteen participants who received DDMM were randomized and boosted with MVA/HIV62B alone (T3; n = 6), MVA/HIV62B and AIDSVAX B/E (T4; n = 6), or AIDSVAX B/E alone (T5; n = 7). Boosts were at months 0 and 4. Participants were followed for safety and immunogenicity for 10 months and were pooled for analysis based on the regimen: MVA-only (T1 + T3), MVA + AIDSVAX (T2 + T4), and AIDSVAX-only (T5). Results: All regimens were safe and well-tolerated. Prior to the boost vaccination, binding antibody and CD4+T-cell responses were observed 7 years after HVTN 205 vaccinations. Late boosting with AIDSVAX, with or without MVA, resulted in high binding antibody responses to gp120 and V1V2 epitopes, with increased magnitude and breadth compared to those observed in HVTN 205. Late boosting with MVA, with or without AIDSVAX, resulted in increased gp140 and gp41 antibody responses and higher CD4+T-cell responses to Env and Gag. Conclusions: Late boosting with AIDSVAX, alone or in combination with MVA, can broaden binding antibody responses and increase T-cell responses even years following the original MVA/HIV62B with or without DNA-priming vaccine.